A viable source of low-latitude Pc3's in the magnetosphere - Yumoto, Kiyohumi (1984)
P(論文) Daytime magnetic pulsations observed at synchronous orbit by GOES 2 are analyzed to determine whether there is a candidate for the source of low-latitude Pc 3's in the outer magnetosphere. Compressional, radially transverse, and azimuthally transverse modes of magnetic pulsations in a wide frequency range exist simultaneously in the outer daytime magnetosphere. The compressional and the transverse modes of the daytime magnetic pulsations observed at GOES 2 are statistically dominant in the Pc 3 and in the Pc 4 frequency ranges, respectively. Some 70 percent of the compressional Pc 3 pulsations at GOES 2 have periods similar to the low-latitude Pc 3's observed at San Gabriel Canyon, which is located ∿ 11°west of GOES 2's longitude at L=1.8. The transverse Pc pulsations at GOES 2 can propagate only into the high-latitude ionosphere. The compressional Pc 3 pulsations at GOES 2 are theoretically expected to propagate across the ambient magnetic field to very low latitudes and to couple with one or more of the followings; (i) a surface wave at the plasmapause (Lpp), (ii) a trapped oscillation of the fast magnetosonic wave in the plasmasphere (L=1.7∿Lpp), (iii) a higher-harmonic standing oscillation of a local field line at mid-latitudes (L=2.0∿Lpp), and (iv) a fundamental standing oscillation at very low latitudes (L=1.1 and 1.7-2.6). Although further research is needed to clarify the wave and propagation characteristics of the low-latitude Pc 3 pulsations, we believe that the compressional Pc 3 magnetic pulsations in the outer magnetosphere are a source of the low-latitude Pc 3 magnetic pulsations. departmental bulletin paper